A Case Report of Herlyn-Werner-Wunderlich Syndrome - Hosseini, Afsaneh (Iranian Journal of Pediatric Surgery, 2023)
Introduction Müllerian duct abnormalities (MDAs) are the most common congenital genital abnormalities in females and included defects ranging from minor anomalies such as bicornuate or septate uterus to major defects such as uterus aplasia (1)Herlyn-Werner-Wunderlich syndrome (HWWS) is a rare müllerian anomaly characterized by uterus didelphys with obstructed hemivagina and ipsilateral renal agenesis. The syndrome is usually associated with non-specific symptoms such as progressive pelvic pain after the menarche, dysmenorrhea, and palpable mass in the vagina caused by hematocolpos and hematometra. Case report: A 15-year-old single patient was admitted with abdominal pain and a feeling of heaviness. On examination of the abdomen and rectum, he had a palpable tactile mass about 10 cm in diameter. Heterogeneously attached to the right side of the uterine body through a base. The size and appearance of the left ovary was normal, but the right ovary was not observed. In the appendix on the right, a complex mass 46 mm in diameter was presented, indicating the presence of a serrated uterine fibroid or ovarian mass. The uterus was normal. Because virgin MRI was performed on abdominal MRI with and without contrast, renal failure and 80x56 mm cystic lesion with several thin internal septa were found in the right appendix. Conclusion The rarity of Herlyn-Werner-Wunderlich syndrome(HWWS) results in complicated diagnostic and therapeutic procedures. Appropriate imaging techniques and correct interpretation is an attempt for faster diagnosis and treatment to avoid complications such as endometriosis and adhesions caused by chronic infections, and infertility. For these cases that had low age, due to the lack of a kidney and also negative impact of multiple surgeries on fertility, it is better the first decision to be made as a group in a medical joint commission. By increasing the number of case reports in the future, the etiology, best diagnostic and treatment methods will be more identified.